PENGARUH IMPLEMENTASI KURIKULUM BERBASIS KKNI TERHADAP PENINGKATAN MUTU PENDIDIKAN PTAIN - Khairiah Khairiah (Universitas Islam Negeri Fatmawati Sukarno, 2015)
The purpose of this study was to determine the influence of KKNI based (Indonesian national qualifications framework) curriculum toward the improvement of the education quality of PTAIN (State collage for islamic studies). The method of discussion done by the author is the observation at IAIN Bengkulu, equipped by literature study that packaged using descriptive qualitative analysis based on some opinions, Thought and reviews from experts in the field of education, academics and education practitioners who are competent. The result shows that the implementation/ execution of KKNI through several stages including preparing the learning achievements, formulating a profile of graduates of study programs, formulating competency standards learning outcomes, formulating the achievement of learning courses, formulating the achiement of course learning outcomes/CLO, finding key concepts and keywords to the achievement of the learning courses, RPKPS development (planning programs and learning activities of the semester): The quality improvement of PTKIN influenced by the implementation / application of KKNI based curriculum through three main factors: (1) the adequacy of educational resources in terms of the quality of staff, cost and means of learning; (2) the quality of the learning process that encourages students to learn effectively and (3) the quality of output in form of knowledge and attitude skills. Then it can be recommended that PTKIN should immediately implement the curriculum of KKNI to improve the education quality of PTKIN